2020
DOI: 10.1111/hae.13915
|View full text |Cite
|
Sign up to set email alerts
|

FIX potency of rFIX‐Albumin fusion protein is underestimated by one‐stage methods using silica‐based APTT reagents

Abstract: Introduction Higher potency is obtained with chromogenic substrate (CS) methods and one‐stage (OS) method with SynthAFax vs silica‐based OS methods on analysis of albutrepenonacog alpha (rFIX fused with albumin, rFIX‐FP). Aim Investigation of the effect of contact activator in search for explanation of discrepancy between methods. Methods Chromogenic Rox Factor IX method and OS methods with Pathromtin SL, SynthAFax or new OS method variants using different phospholipid emulsions and addition of either colloida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…28,[46][47][48][49][50] For EHL-FIX products, OS/CS assay discrepancies can be pronounced. 13,[51][52][53][54] This complexity has led to guiding recommendations for potency assignment of recombinant FVIII/FIX products. 55 A probable root cause underlying many of these assay discrepancies is a deviation from the like-vs-like principle: that is, defined molecular differences between nonnative FVIII/FIX analytes and native FVIII/FIX calibrators, leading to divergent behavior in the assays.…”
Section: Discussionmentioning
confidence: 99%
“…28,[46][47][48][49][50] For EHL-FIX products, OS/CS assay discrepancies can be pronounced. 13,[51][52][53][54] This complexity has led to guiding recommendations for potency assignment of recombinant FVIII/FIX products. 55 A probable root cause underlying many of these assay discrepancies is a deviation from the like-vs-like principle: that is, defined molecular differences between nonnative FVIII/FIX analytes and native FVIII/FIX calibrators, leading to divergent behavior in the assays.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was consistent with Park et al, both patients showed normal APTT, using reagents from Diagnostica Stago. A recent study showed discrepancies on the determination of FIX:C of rFIX fused with albumin (rFIX-FP) with one-stage and chromogenic methods [14]. Recent studies found that different APTT reagents showed highly variable sensitivity to single factor deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…[66][67][68] Interestingly, it has been recently proposed that the latter is due to impaired activation of rFIX-FP during Pathromtin SL (and colloidal silica)-based OSC measurements. 69 On the basis of the data published to date, an OSCA for the measurement of Idelvion appears to be preferable; however, the above-described aPTT reagents should not be applied (►Table 1).…”
Section: Albutrepenonacog Alfa (Idelvion)mentioning
confidence: 99%